Quaternary Large Mammals from the Granada Geopark: A Magnificent Record with Examples of Geoconservation. - Alfonso Arribas Herrera; Guiomar Garrido Álvarez; José Antonio Garrido García; Francisco Juan García Tortosa; Cristobal Medialdea Pérez (Geoconservation Research)
Granada Geopark, covering almost all of the Guadix-Baza basin, contains an exceptional and near-continuous fossil record of the evolution of Pliocene to middle Pleistocene land mammals (5–0.5 Ma). This period covers the endorheic (closed drainage basin) stage of this geological basin and, in this chronological framework, its record of the Quaternary period, mainly the Early Pleistocene, is outstanding.